Assessment of visual evoked potential characteristics and their relationship with functional parameters in different stages of primary open angle glaucoma - L.M. Stotska (Ukrainian Society of Ophthalmologists, 2016)
Background: Studies of structural and neurophysiological processes in the superior visual system of patients with primary open-angle glaucoma (POAG) help in detecting primary structural lesions in this disorder. Investigation of brain evoked potentials provides the most important information about the processes in the visual cortex, and that of visual evoked potentials (VEP) provides us with the most valuable information. It is neurophysiological studies that often identify the nervous system changes developing during a long silent period before features of clinical disease become evident, which is especially important for early diagnosis of the glaucoma process. Lately, foreign and national ophthalmologists have been paying special attention to the diagnosis of pathologic retinal changes in different stages of POAG. Purpose: To assess VEP characteristics and their relationship with functional parameters in different stages of POAG. Materials and Methods: One hundred and eighty six patients (358 eyes) underwent a clinical and neurophysiological study at the Filatov Institute of Eye Diseases. The study group comprised 156 patients (81 females and 75 males; mean age, 56.8 ± 4.26 years) with different POAG stages, whereas the control group comprised 30 patients without POAG. The RETIscan system (Roland Consult, Wiesbaden, Germany) was used to perform neurophysiological studies (pattern and flash VEP). Results: Compared to controls, preglaucoma and mild-stage POAG patients had statistically significantly increased VEP N75-P100 peak-to-peak amplitude (12.80 ± 4.57 µV (140.6%) and 14.84 ± 3.09 µV (180%), respectively р<0.05), whereas moderate-stage and severe-stage POAG patients had decreased VEP N75-P100 peak-to-peak amplitude (1.61±1.32 µV (69.62%) and 2.34±0.61 µV (55.85%), respectively, р<0.05). The VEP N75, Р100, and N135 latencies in preglaucoma and mild-stage POAG patients were not statistically significantly different from those of controls. The VEP P100 latency in moderate-stage POAG patients was statistically significantly increased (17.12%, р<0.05) compared to controls. Compared to controls, severe-stage POAG patients had statistically significantly increased P100 latency and N135 latency (26.88% and 13.44%, respectively; р< 0.05), and decreased visual system sensitivity (phosphene threshold current) (80.0 ± 8.25 µA; 22.68%; р<0.05). The visual system sensitivity (phosphene threshold current) in patients with preglaucoma, mild- and moderate-stage POAG was within the normal range. In patients with pre-glaucoma, a correlation was found between pattern VEP P100 latency and visual field index (VFI) (rho = 0.11, p < 0.05) as well as between P100-N75 peak-to-peak amplitude and Humphrey mean deviation (MD) (rho = 0.6, p<0.05). No correlation was found between pattern and flash VEP parameters and such clinical parameters as VFI, MD, cup width and intraocular pressure in mild, moderate and severe POAG. Conclusions: Investigation of neurophysiological processes in retinal ganglion cells and the use of VEP in clinical practice are important for the diagnosis of glaucoma before the clinical symptoms manifest.